2008
DOI: 10.1002/nme.2363
|View full text |Cite
|
Sign up to set email alerts
|

A 3D BEM model for liquid sloshing in baffled tanks

Abstract: SUMMARYThe present work aims at developing a boundary element method to determine the natural frequencies and mode shapes of liquid sloshing in 3D baffled tanks with arbitrary geometries. Green's theorem is used with the governing equation of potential flow and the walls and free surface boundary conditions are applied. A zoning method is introduced to model arbitrary arrangements of baffles. By discretizing the flow boundaries to quadrilateral elements, the boundary integral equation is formulated into a gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…Firouz-Abadi [18] provided a diagram summarizing the dimensionless sloshing frequencies as a function of the baffle height in a rectangular tank based on a model test with the baffle located in the middle of the tank, shown in Figure 4. In this diagram, the weir is regarded as a vertical baffle, and the natural frequencies could be predicted.…”
Section: Rectangular Vessel With Vertical Baffle Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Firouz-Abadi [18] provided a diagram summarizing the dimensionless sloshing frequencies as a function of the baffle height in a rectangular tank based on a model test with the baffle located in the middle of the tank, shown in Figure 4. In this diagram, the weir is regarded as a vertical baffle, and the natural frequencies could be predicted.…”
Section: Rectangular Vessel With Vertical Baffle Modelmentioning
confidence: 99%
“…The diagram of dimensionless sloshing frequency against the baffle height in a rectangular tank is displayed in [18]. This is based on a model test on a baffle located in the middle of the tank and the 1st mode natural frequencies could be calculated in this way.…”
Section: With/without Consideration Of Baffle Position (For Region 2)mentioning
confidence: 99%
“…In their study, the vertical baffle is a more effective tool in reducing the sloshing amplitude. In the same year, A BEM (Boundary element method) model for liquid sloshing in a baffled tank was adopted by Firouz-Abadi et al [17]. The determinations of the natural frequencies and mode shapes of liquid sloshing in baffled tanks with arbitrary geometries were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A similar conclusion was found by Idir et al, 2009 who showed that a hump topography is more effective at attenuating the energy of a forcing than a flat bottomed TLD. The natural frequencies of sloshing modes in baffled three-dimensional tanks has also been examined numerically using boundary integral methods (Firouz-Abadi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%